Ultra-low leakage static random access memory design - Didigam Anitha; Mohd. Masood Ahmad (Institute of Advanced Engineering and Science, 2023)
An ultra-low leakage static random-access memory (SRAM) cell structure with 8 transistors is proposed in this paper. Compared to the 6T SRAM and other existing 8T SRAM cells, leakage power of the proposed cell in hold mode reduced significantly. The stability parameters of the proposed cell are calculated using butterfly method and also N-curve method. Proposed SRAM achieves better write margin with slightly less read margin than 6T SRAM. Proposed technique consumes 790 PW of power in hold mode, which is very less compared to other existing techniques. Therefore, the proposed cell is appropriate for hold mode applications. The simulations are carried out by using Cadence (Virtuoso Schematic and layout editor) tools with GPDK45-nm technology.